2018
DOI: 10.3390/cancers10090282
|View full text |Cite
|
Sign up to set email alerts
|

DNA Replication Licensing Protein MCM10 Promotes Tumor Progression and Is a Novel Prognostic Biomarker and Potential Therapeutic Target in Breast Cancer

Abstract: Breast cancer is one of the most common malignancies in women worldwide. In breast cancer, the cell proliferation rate is known to influence the cancer malignancy. Recent studies have shown that DNA replication initiation/licensing factors are involved in cancer cell proliferation as well as cancer cell migration and invasion. Licensing factors have also been reported as important prognostic markers in lung, prostrate, and bladder cancers. Here, we studied the role of MCM10, a novel licensing factor, in breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…A similar trend for MCM10 has also been reported in cervical cancer, and overexpression of MCM10 is a stage‐specific marker, indicating that MCM10 is critical in the progression of cervical cancer . One mutually supportive report by Mahadevappa et al has suggested the role of MCM10 in breast cancer progression. Their findings and our research data jointly indicated that MCM10 is a potential prognostic marker and target for breast cancer therapy.…”
Section: Discussionmentioning
confidence: 57%
“…A similar trend for MCM10 has also been reported in cervical cancer, and overexpression of MCM10 is a stage‐specific marker, indicating that MCM10 is critical in the progression of cervical cancer . One mutually supportive report by Mahadevappa et al has suggested the role of MCM10 in breast cancer progression. Their findings and our research data jointly indicated that MCM10 is a potential prognostic marker and target for breast cancer therapy.…”
Section: Discussionmentioning
confidence: 57%
“…Recent researches have unveiled that MCM10 plays a key functional role as a DNA binding scaffold for guarding against replication stress in replication, and is involved in maintaining genome integrity, indicating that its dysregulation may contribute to genomic instability, which can induce abnormal proliferation and cancer progression in turn [41,42] . Over-expression of MCM10 had been found in a variety of malignancies, such as prostate [19] , breast [20] , pancreatic [21] , lung [43] and cervical [44] cancers. In cancer cell lines, knockdown of MCM10 expression showed noticeably decreased tumor properties such as proliferation, migration and colony formation, but increased cell apoptosis [19,20] .…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression of MCM10 had been found in a variety of malignancies, such as prostate [19] , breast [20] , pancreatic [21] , lung [43] and cervical [44] cancers. In cancer cell lines, knockdown of MCM10 expression showed noticeably decreased tumor properties such as proliferation, migration and colony formation, but increased cell apoptosis [19,20] . Several lines of evidence showed that MCM10 was of prognostic relevance for predicting survivals in malignant tumors [19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations